1994
DOI: 10.3109/08910609409141362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gluconic Acid on Human Faecal Bacteria

Abstract: Gluconate was fermented selectively by the Bijidohacterium adolescentis group and some species of other genera, including Clostridium clostridiiforme, C. innocuum, Propionibacterium acnes, Megasphaera elsdenii, Enterococcus jaecium and Klebsiella pneumoniae; however it was not utilised by most other bacteria including the Bacteroidaceae. No other organic acid salts were utilised by B. adolescentis. These salts weakly inhibited the growth of C. perjringens in vitro, as did gluconate. The absorption rate of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 9 publications
1
30
1
1
Order By: Relevance
“…It is a functional ingredient that promotes the growth of Lactobacillus bifidus in the intestine, as do oligosaccharides. 7) To confirm a new use for gluconate, we investigated its suppressive effect on bitter taste. Three substances were used as bitter tastants, QHCl, which is used as a medicine, and caffeine and naringin, which are added to or found in food.…”
Section: Discussionmentioning
confidence: 99%
“…It is a functional ingredient that promotes the growth of Lactobacillus bifidus in the intestine, as do oligosaccharides. 7) To confirm a new use for gluconate, we investigated its suppressive effect on bitter taste. Three substances were used as bitter tastants, QHCl, which is used as a medicine, and caffeine and naringin, which are added to or found in food.…”
Section: Discussionmentioning
confidence: 99%
“…Gluconic acid is used as a flavoring agent (Boutraux, 1978). Asano et al (1994) found that gluconic acid promotes the growth of Lactobacillus bifidus, as do oligosaccharides. Furthermore, Morita et al (1994) reported that calcium gluconate improves bread dough.…”
mentioning
confidence: 98%
“…Of course, a part of beneficial effect of OA is mediated by decreasing microbial populations in intestine. In this regard, it has been reported that gluconic acid improved nutrient digestibility via reducing pathogenic intestinal bacteria (Asano et al, 1994).…”
Section: Discussionmentioning
confidence: 99%